Perinatal Mortality: A Mirror Image of Maternal Health (Medical Forum Monthly, 2024)
Objective: Perinatal mortality usually reflects health status of mother and is indicator of quality of care received by mother during her period of gravidness and fetus at birth. We carried out this study to evaluate the magnitude of perinatal mortality at our institute and its contributing factorsStudy Design: Cross sectional studyPlace and Duration of Study: This study was conducted at Obst. & Gynae Unit II and Unit of Pediatric Medicine, Chandka Medical College hospital Larkana from 1st January 2012 to 31st December 2012.Materials and Methods: Women who delivered after 24 completed weeks were selected from labour room. Perinatal deaths including stillbirths and early neonatal deaths up to 7 days of life were studied. Outcome variables like maternal age, parity, communal standing and booking status were taken in to consideration. Complications arising during pregnancy or any medical illness, details of labour, fetal condition at birth were also noted.Results: During the study period 4818 women delivered. There were 473 perinatal deaths with a perinatal mortality rate of 98/1,000 live births. Among these women only 9% were booked, while 91% un-booked. Perinatal death rate was more seen in maternal age group between21-30 years that were 51%. Women having parity of 2-5 had highest perinatal mortality of about 44%. Gestational age from 31-36 weeks contributed about 46%. Most prevalent condition reportedly causing perinatal death was prolonged and obstructed labour which added 30% of total, followed by antepartum hemorrhage causing 18% of perinatal deaths. Hypertensive disorders and other maternal medical diseases contributed about 15.5% and 6.5% respectively.10% fetuses died of congenital anomalies.11% neonatal septicemia seen. Unexplained still births seen in 9% of total.Conclusion: Perinatal mortality is stagnantly high among mothers with poor health even having no access for antenatal, intra partum and postnatal care. Unfortunately they report to hospital when already had developed some complication. Awareness programs at community level, training health workers providing facilities at remote health centers can make the lot of difference.